Determinação da taxa de respiração em sementes de soja pelo método da titulação - Crispim, J. E.; Martins, J. C.; Pires, J. C.; Antonio, C.; Cavariani, REC (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1994)
This trial was carried out under laboratory conditions, with three lots of Iguacu soybean seeds, to determine the respiration rate by the titulation method. A randomized complete block design was used, with four repetitions, each one of them with 50 seeds and a control without seeds for each lot. The seeds were placed in gerbox with 40 mi of KOH 0.1N, on distilled water wet blotting paper for fixing the CO2 produced by seeds respiration. The material was placed in germinator at constant 25 degrees C for 16, 24 and 48 hours. After these periods, the titulation of the fixative solution was performed with HCl 0.1N to check the respiration rate. The most deteriorated seeds were those that presented the highest respiration rates, which were measured in mg of CO2/g of dry matter, when compared with the most vigorous lots. The titulation method was suitable for the evaluation of soybean seed respiration rate because the final results separated the lots in three different quality levels that were compatible with the results obtained from the accelerated aging and emergence.

O presente trabalho foi conduzido em condições de laboratório, utilizando-se três lotes de sementes de soja da cultivar Iguaçu, com o objetivo de determinar a taxa de respiração, pelo método da titulação. O delineamento experimental foi o de blocos inteiramente casualizados, com quatro repetições, cada uma delas constando de 50 sementes de cada lote e uma testemunha sem sementes em cada lote. As sementes foram acondicionadas em gerbox contendo 40 ml de KOH 0,1N, sobre papel mata-borrão umedecido com água destilada, para fixação do CO2 produzido pela respiração das sementes. O material foi mantido em germinador com temperatura constante de 25°C, por 16, 24 e 48 horas, após o que, foi efetuada a titulação da solução fixadora com HCl 0,1N para verificação da taxa de respiração. Os resultados mostraram que as sementes mais deterioradas foram as que apresentaram maior taxa de respiração, medida em mg de CO2/g de matéria seca, quando comparadas com lotes mais vigorosos. O método da titulação mostrou-se conveniente para avaliação da taxa de respiração de sementes de soja.
Determination of soybean seed respiration rate by the titulation method
Determination of soybean seed respiration rate by the titulation method
Keywords: SEED QUALITY; CO2 FIXING; GERMINATION; GERMINATOR; VIGOR